The occurrence of drought and its probabilities in the Baixada Fluminense, Rio de Janeiro - Menezes, Dinah Mochel de; Ellis, Jacques; Mueller, Sven Koster (Pesquisa Agropecuaria Brasileira, 2014)
This study has tabulated the consecutive days without rain for the thirty year period of 1941 through 1970. The data were taken from the daily records of the Climatological Section of the Instituto de Pesquisa Agropecuária do Centro-Sul. The data were analized statistically utilizing the first order Markov chain probability model. The probabilities are derived for the Baixada Fluminense area (Rio de Janeiro). The major dry periods were recorded in the months of June, July and August. The range of probabilities of dry periods of 5 days duration or longer were from 10% in December to 51% in August. The transition (months) were noted in April and May and again in September.